ADAM28 is expressed by epithelial cells in human normal tissues and protects from C1q‐induced cell death. (26th March 2016) - Miyamae, Yuka; Mochizuki, Satsuki; Shimoda, Masayuki; Ohara, Kentaro; Abe, Hitoshi; Yamashita, Shuji; Kazuno, Saiko; Ohtsuka, Takashi; Ochiai, Hiroki; Kitagawa, Yuko; Okada, Yasunori
Abstract : ADAM28 (disintegrin and metalloproteinase 28), which was originally reported to be lymphocyte‐specific, is over‐expressed by carcinoma cells and plays a key role in cell proliferation and progression in human lung and breast carcinomas. We studied ADAM28 expression in human normal tissues and examined its biological function. By using antibodies specific to ADAM28, ADAM28 was immunolocalized mainly to epithelial cells in several tissues, including epididymis, bronchus and stomach, whereas lymphocytes in lymph nodes and spleen were negligibly immunostained. RT‐PCR, immunoblotting and ELISA analyses confirmed the expression in these tissues, and low or negligible expression by lymphocytes was found in the lymph node and spleen. C1q was identified as a candidate ADAM28‐binding protein from a human lung cDNA library by yeast two‐hybrid system, and specific binding was demonstrated by binding assays, immunoprecipitation and surface plasmon resonance. C1q treatment of normal bronchial epithelial BEAS‐2B and NHBE cells, both of which showed low‐level expression of ADAM28, caused apoptosis through activation of p38 and caspase‐3, and cell death with autophagy through accumulation of LC3‐II and autophagosomes, respectively. C1q‐induced cell death was attenuated by treatment of the cells with antibodies against the C1q receptor gC1qR/p33 or cC1qR/calreticulin. Treatment of C1q with recombinant ADAM28 prior to addition to culture media reduced C1q‐induced cell death, and knockdown of ADAM28 using siRNAs increased cell death. These data demonstrate that ADAM28 is expressed by epithelial cells of several normal organs, and suggest that ADAM28 plays a role in cell survival by suppression of C1q‐induced cytotoxicity in bronchial epithelial cells. Abstract : ADAM28 is over‐expressed in human lung and breast carcinomas, and has been implicated in proliferation and progression of cancer. Expression of ADAM28 was thought to be specific to lymphocytes in normal tissues, but here the authors demonstrate that this metalloprotease is also expressed by epithelial cells in normal tissues, including the epididymis, bronchus and stomach. They also report that ADAM28 binds to C1q, and that C1q‐induced cell death in bronchial epithelial cells is attenuated by ADAM28, suggesting that the latter protease plays a role in cell survival by suppressing C1q‐induced cytotoxicity in bronchial epithelial cells.